A low-cost and small USV platform for water quality monitoring. (October 2019) - Jo, Wonse; Hoashi, Yuta; Paredes Aguilar, Lizbeth Leonor; Postigo-Malaga, Mauricio; Garcia-Bravo, José M.; Min, Byung-Cheol
Graphical abstract: Abstract: We propose a new, fully open-source, low-cost, and small-sized Unmanned Surface Vehicle (USV) for measuring near-surface water quality in real time in various environments. Existing commercial USVs are expensive and not fully based on open-source hardware, making it difficult to purchase them and to modify their designs and programming to suit various environments. In contrast, the USV platform proposed in this paper is completely open-source, from hardware to software; most parts of the platform can be 3D-printed, and it can be easily modified and upgraded in terms of both design and programming. The platform is equipped with off-the-shelf water sensors for acquiring data like as pH, turbidity, and temperature to measure water quality in real water resources (such as ponds, reservoirs, and lakes). Furthermore, we provide an Android application through which users can easily control the USV via Bluetooth and display the sensor and GPS data the platform generates. We validated the performance of the platform in terms of usability, mobility, and stability through field experiments in various locations, including both the USA and Peru. Moreover, we present a potential application and approach in which this platform can navigate autonomously by utilizing the Robot Operating System (ROS) and Bluetooth protocols.